Heidegger e o problema da superação da metafísica: a Gelassenheit como sua resolução final - Ruggeri, Sabrina (2020)
Our work addresses the problem of overcoming metaphysics in Heidegger – how the very meaning of the notion of metaphysics found a tortuous fate in his work and how the understanding of the effectiveness, and even the possibility of its overcoming was each time expressed in Heideggerian thinking. The complexity of the issue deepens when post-Kehre Heidegger’s position is that metaphysics is an integral part of the grant of Being as its unavoidable character of retraction, thus setting the need for a torsion in the very category of overcoming (which is now understood as Verwindung). The problem then becomes how to answer what this overcoming is and how to execute it after all, when thought recognizes the very truth of metaphysics and its belonging to this original negation. Our objective is thus that, after establishing the necessary basis for the proper understanding of the problem of metaphysics in its real complexity and depth for Western humanity, to develop the hypothesis that the final resolution to this problem in Heidegger's thought is found in the figure of the 50s Gelassenheit. Metaphysics here becomes synonymous with technology and its overcoming now answers the problem of the possibility of an exit from the domain of the will – the notion of will is thus elevated to the maximum position of a critical element in Heidegger's thought as the unifying principle of the history of forgetfulness of Being, while releasement [Gelassenheit] must guide the first steps towards a transformed sojourn for humans on this planet. Our methodology mainly follows the indications of a retrospective reading of the Heideggerian work, which starts from the semantic and theoretical changes established by the Contributions (in short, the abandonment of the method of hermeneutical phenomenology and its intrinsic transcendentalism) to reinterpret and reevaluate the fractures of Being and Time as the first articulated proposal of a resetting for the question of Being. Thus, as an assumption of a profound unity of the Heideggerian philosophical project, even with the diagnosis of radical variations on how Being itself is each time understood, as well as the way of conducting its essential interrogation. The central conclusion is that Gelassenheit constitutes Heidegger's ultimate contribution to the construction of a post-metaphysical paradigm since it both overcomes the notion of representation as the metaphysical essence of thought and its related posture of dominance as the basic relationship with the world of things.